Influence of Micro-Structure on the Fatigue Crack Propagation in Bridge Steel - Seitl, Stanislav; Miarka, Petr; Pokorný, Pavel; Fintová, Stanislava; Klusák, Jan (MDPI, 2018)
The use of high strength steels (HSS) allows designing lighter, slenderer and simpler structures with high structural performance. In general, the use of HSS leads to weight reduction of the whole structure, which compensates the higher cost of such a material comparing to the conventional construction steels. Knowledge of the fatigue resistance of material plays the key role during design and maintenance of the bridge structures. This contribution brings a comparison of the fatigue crack growth resistance of S355 J0 steel. Differences in microstructure and the texture of material structure could generally play a role in the fatigue crack growth. This study shows that in the case of studied steel texture of material structure has an influence on material fatigue behavior in Paris’ law regime.

The use of high strength steels (HSS) allows designing lighter, slenderer and simpler structures with high structural performance. In general, the use of HSS leads to weight reduction of the whole structure, which compensates the higher cost of such a material comparing to the conventional construction steels. Knowledge of the fatigue resistance of material plays the key role during design and maintenance of the bridge structures. This contribution brings a comparison of the fatigue crack growth resistance of S355 J0 steel. Differences in microstructure and the texture of material structure could generally play a role in the fatigue crack growth. This study shows that in the case of studied steel texture of material structure has an influence on material fatigue behavior in Paris’ law regime.
Influence of Micro-Structure on the Fatigue Crack Propagation in Bridge Steel
Keywords: bridge steel; Paris’ law; microstructure; stress intensity factor; fatigue properties; S355 J0; bridge steel; Paris’ law; microstructure; stress intensity factor; fatigue properties; S355 J0